To solve the quadratic equation 2x^2 - 5x - 3 = 0, we can use the quadratic formula:
x = (-b ± √(b^2 - 4ac)) / 2a
Where a = 2, b = -5, and c = -3.
Plugging in the values, we get:
x = (5 ± √((-5)^2 - 4*2*(-3))) / 2*2
x = (5 ± √(25 + 24)) / 4
x = (5 ± √49) / 4
x = (5 ± 7) / 4
This gives us two possible solutions:
x1 = (5 + 7) / 4 = 3
x2 = (5 - 7) / 4 = -0.5
So, the solutions to the equation 2x^2 - 5x - 3 = 0 are x = 3 and x = -0.5.
Please provide the graph so I can further assist you.
) Solve 2x2−5x−3=0and enter solutions below. 2) Push the "Graph It" Button to see a graph of y=2x2−5x−3
1 answer